PENGARUH AKULTURASI BUDAYA BARAT MELALUI PERKEMBANGAN INSTRUMEN KEYBOARD TERHADAP MUSIK ETNIS BATAK TOBA - Lamberto Auro Sinaga; Christian Timothy hasugian (Universitas Hamzanwadi, 2026)
This research discusses the influence of Western cultural acculturation through the development of keyboard instruments on Toba Batak ethnic music. Batak Toba ethnic music is one of Indonesia's rich cultural heritages, with rich melodies, rhythms, and lyrics that reflect the history, beliefs, and lives of the Batak Toba people. This research was conducted to help understand how Western cultural influences have affected Batak Toba ethnic music, especially in the development of instruments used and the development of Batak Toba ethnic music. This research uses a quailitative method with an ethnographic reset design and data sources include interviews, observations, and documentation. The results showed that the use of keyboard instruments has had a significant impact on Toba Batak ethnic music. Keyboards have enabled Batak Toba musicians to produce a variety of sounds and harmonies that cannot be achieved with traditional musical instruments. This research helps to understand how Western cultural influences have affected Batak Toba ethnic music, especially in the development of the instruments used and the development of Batak Toba ethnic music. The results of this research are expected to improve the quality of Batak Toba music and as an education to the community to maintain and defend Batak Toba Culture.